Management of Avian Influenza H9N2 Vaccination in Broiler Chickens at JAPFA COMFEED Myanmar Pte Ltd. - Verian, Bagas Ridjalu; Prasetyo, Dodik; Adrenalin, Sruti Listra; Wuragil, Dyah Kinasih; Cahyo, Budi Nur (Veterinary Biomedical and Clinical Journal, 2024)
Avian influenza virus subtype H9N2 (AIV-H9N2) has been a concern for poultry health in the last 20 years. The virus emerged in domestic poultry in the mid-1990s and has been reported in several Asian countries, including Myanmar. AI subtype H9N2 caused huge economic losses to the poultry industry in the form of respiratory distress and 25% weight loss in broiler chickens. This study discusses the administration of Avian Influenza (AI) H9N2 strain inactivated vaccine to commercial broiler chickens at JAPFA COMFEED Myanmar Pte Ltd. The vaccination process was carried out through subcutaneous injection in the neck and intramuscular injection in the pectoralis musculus in the chest area of chickens at 11 days of age, with a dose of 0.5 ml per chicken. The vaccine used was VAKSIMUNE® AI H9 which uses oil as the emulsion material. Results from the HI serology test showed that 6 cages from Myothar and Wah Net Chaung farms showed protective antibody titers against Avian Influenza H9N2 virus at 30-40 days of age, with normal titer values or ≥24. This indicates that the AI subtype H9N2vaccine used is an effective antigen, capable of stimulating the broiler immune system, and has implications for increasing antibodies every week. This study contributes to the understanding of AI H9N2 vaccination management in commercial broilers at JAPFA COMFEED Myanmar Pte Ltd. With positive results in the serology test, it can be concluded that vaccination using VAKSIMUNE® AI H9 is effective in protecting broilers from Avian Influenza H9N2 infection, providing strong support to the sustainability of production and animal health in a commercial farm environment.